Communication Strategies used by EFL Students in Their Presentation - Christina I.T. Panggabean; Agus Wardhono (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2017)
In the process of communication using the target language, EFL students usually have some problems to communicate their ideas. To cope with the problems they encounter, the students will try to use certain communication strategies so that their ideas can be clearly explained. This paper reports the results of the research on the communication strategies used by EFL students in their presentation. This study is designed as a qualitative research. The subjects of the study were the seventh semester students representing more and less proficient students in their classes. The data are the communication strategies employed by the students when they had oral presentation for Cross Cultural Understanding course. The results of the research reveal that the more proficient students used eleven types of communication strategies and the less proficient students used thirteen types of communication strategies. Some interlingual strategies, code switching, appeal for help, and some non linguistic strategies were used by the students. It is also found that the more proficient students used more L2 based strategies, and L1 terms occurred in the language of all levels of proficiency. Despite the differences, the students need to be encouraged to use more compensatory strategies to achieve their communication goal.